Dead Poets Society [videorecording (Blu-Ray)] - Schulman, Tom; Charles, Josh, 1971-; Leonard, Robert Sean, 1969-; Hawke, Ethan, 1970-; Williams, Robin, 1951-2014; Seale, John, 1942-; Jarre, Maurice (Touchstone Home Entertainment, 2012)
For generations, Welton Academy students have been groomed to live lives of conformity and tradition, until new professor John Keating inspires them to think for themselves, live life to the fullest, and 'Carpe Diem.' This unconventional approach awakens the spirits of the students, but draws the wrath of a disapproving faculty when an unexpected tragedy strikes the school. Featuring new interview footage with director Peter Weir, Ethan Hawke, Robert Sean Leonard, and many others.